Productividad informativa en situaciones de crisis social: los casos de ABC, El País y La Razón durante el 11-M - Carvajal Rivera, Julio (Estudios sobre el Mensaje Periodístico, 2008)
When there happen critical events of social and political order in the democratic societies, the performance and the productivity of the mass media of masses suffer important changes. In addition, these are questioned respect of the social responsibility that has corresponded to them in the conflict, specifically as for its ‘informative truth’. The events happened in the morning of March 11, 2004 in the trains of Madrid, left dead, thousands of injured and pain in the Spanish society. During these three days of social and political crisis a role reached gravitated the management recovered by the media of social communication; the written press is special, from the perspective of your organization and informative production.